Albumin bound and alpha 2-macroglobulin bound zinc concentrations in the sera of healthy adults. Issue 9 (September 1984) - Foote, J W; Delves, H T
Abstract : Reference ranges for albumin bound and alpha 2-macroglobulin bound zinc concentrations have been determined in a study of sera obtained from 134 healthy adults. The concentrations of zinc bound to alpha 2-macroglobulin were remarkably constant with a mean (+/-SD) of 2.4 +/- 0.6 mumol/l; the variations in total serum zinc concentrations were almost entirely accounted for by variations in the zinc associated with albumin. There were no sex related differences in the transport of zinc in serum; neither was this sensitive to the use of oral contraceptives. These data provide a baseline for further investigations into the effects of zinc deficiency on the serum transport of the metal.